Nonmuscle Tissues Contribution to Cancer Cachexia - Josep M. Argilés; Britta Stemmler; Francisco J. López-Soriano; Silvia Busquets (Mediators of Inflammation)
Cachexia is a syndrome associated with cancer, characterized by body weight loss, muscle and adipose tissue wasting, and inflammation, being often associated with anorexia. In spite of the fact that muscle tissue represents more than 40% of body weight and seems to be the main tissue involved in the wasting that occurs during cachexia, recent developments suggest that tissues/organs such as adipose (both brown and white), brain, liver, gut, and heart are directly involved in the cachectic process and may be responsible for muscle wasting. This suggests that cachexia is indeed a multiorgan syndrome. Bearing all this in mind, the aim of the present review is to examine the impact of nonmuscle tissues in cancer cachexia.